Впринципе вот... понятно думаю тебе
-1,2(-3x-y)+7,9x-0,7(4y-x)=3,6x+1,2y+7,9x-2,8y+0,7x=12,2x-1,6y=(12,2*0,2)-(1,6*0,6)=2,44-0,96=1,48
Эм.......................где картинка или что то подобное?
45-16=29
29×2=58
69+27=96
96:8=12
22x+x-10=59
23x=59+10
x=69:23
x=3
Ответ: 3
(x+2,4):8=2,3
x+2,4=2,3*8
x=18,4-2,4
x=16
Ответ: 16
<span>(0,95x-1,82):1,7=3,4
</span>0,95x-1,82=3,4*1,7
0,95x-1,82=5,78
0,95x=7,6
x=7,6:0,95=760:95
x=8
Ответ: 8
(0,85x-1,72):1,3=2,6
0,85x-1,72=3,38
0,85x=3,38+1,72
0,85x=5,1
x=5,1:0,85=510:85
x=6
Ответ: 6